Akad Murakkab dalam Produk Keuangan Syariah - Kholijah, Siti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
The most important thing for creating sharia banking and financial products in addressing the demands of modern society is the development of multiple agreement.The form of a single agreement is not able to respond to contemporary financial transactions. Multiple agreement method should be superior in product development. Agreement in sharia transaction are modified from the exciting agreements in which such agreements are found in almost all sharia product. Multiple Agreement(al-UqudÂ  al- Murakkabah) is one of contempory in Islamic banking whose implementation develops in line with business developments.